2017
DOI: 10.4102/sajhivmed.v18i1.712
|View full text |Cite
|
Sign up to set email alerts
|

Condom migration after introduction of pre-exposure prophylaxis among HIV-uninfected adolescents in South Africa: A cohort analysis

Abstract: BackgroundApproximately 3 million adolescents and young adults (AYA), between the ages of 15 years and 24 years, are living with HIV in sub-Saharan Africa. The use of pre-exposure prophylaxis (PrEP) may be a promising HIV prevention tool to bridge the high-risk years of AYA between sexual debut and adulthood.ObjectivesConcerns have been raised that the use of PrEP could lead to an increase in sexual risk behaviour and sexually transmitted infections in general and less condom use in particular among adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is encouraging that approximately 50% of participants had “high” adherence based on TFV‐DP DBS concentrations of ≥700 fmol/punch and in combination with self‐reported consistent condom use increased the overall protection to 68%. This cohort showed that with service delivery of an HIV prevention package, an increase in proportion of condom use was seen, contrary to speculated concerns of PrEP reducing condom use [48]. However, it is acknowledged that condom use can only be measured by self‐report.…”
Section: Discussionmentioning
confidence: 96%
“…It is encouraging that approximately 50% of participants had “high” adherence based on TFV‐DP DBS concentrations of ≥700 fmol/punch and in combination with self‐reported consistent condom use increased the overall protection to 68%. This cohort showed that with service delivery of an HIV prevention package, an increase in proportion of condom use was seen, contrary to speculated concerns of PrEP reducing condom use [48]. However, it is acknowledged that condom use can only be measured by self‐report.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequent publications have similarly shown increases in condomless sex and sexual risk after PrEP initiation among MSM. 17 , 20 , 21 Of the few studies identified among MSM that recruited couples, none assessed longitudinal changes in sexual behaviors after PrEP initiation. Cross-sectional and qualitative data from couples in the United States and Taiwan, however, indicate intention by some HIV-negative men to use condoms less often or not at all with their primary partner or other partners if they started PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Ndinga-Mavumba and Pharoah (2008) state that South Africa has reached the peak of the AIDS pandemic, and sexual behavior change is non-negotiable for moving forward in tackling the disease. HIV-prevention programs aimed at empowering youths are critically needed as young adults are disproportionally at higher risk of HIV infection (Maljaars et al, 2017). LoveLife (2020) advocates the holistic engagement of youths in HIV-prevention programs by addressing issues such as leadership, activism, agency, self-awareness, poverty, gender inequality, positive role models and effective communication.…”
Section: Literature Review 21 Prevention Of Hiv Transmissionmentioning
confidence: 99%
“…Moreover, in understanding youths, it is also vital to recognize that many developmental milestones converge at this stage of their life such as increased cognitive development, psychological, social and structural transitions (Maljaars et al, 2017). Van Dyk, Tlou and Van Dyk (2017) point out that as youths develop; they need support in building their decisionmaking skills, especially given the peer pressure and personal stress they encounter.…”
Section: Literature Review 21 Prevention Of Hiv Transmissionmentioning
confidence: 99%
See 1 more Smart Citation